PENGARUH MODEL PEMBELAJARAN CIRC DALAM MENINGKATKAN KETERAMPILAN MEKANIS MEMBACA WACANA SISWA KELAS VII SMP NEGERI 2 BATANGTORU - Dedi Pulungan (Universitas Negeri Medan, 2019)
Abstract This study aims to describe the effect of using the CIRC learning model in improving the mechanical skills reading discourse in grade VII students SMP Negeri 2 Batangtoru. Based on the results the study aimed that the use CIRC learning model has an influence in improving the technical skills reading discourse. Before the use the CIRC learning model, the pretreatment test results in a student's grade point average was 65.18 with a mastery learning criteria 21.43%. After using the CIRC learning model, in the first cycle the results average grade of students is 68.75, the value has experienced an increase 6.07% when compared with the pre-action scores, with mastery learning student 63.57%. the second cycle was carried out with the expectation ≥ 70% of students being able to achieve a value ≥ 70, the result was that the average grade reached 79.82 which means there was an increase from pre-action 20.96% with the completion criteria of learning students 85.71%. From the results of the research carried out, it can be concluded that after learning with the CIRC model has been carried out, it has an effect on improving the results mechanical reading skills in the discourse grade VII students SMP Negeri 2 Batangtoru. Keywords: CIRC learning model, mechanical skills, reading discourse